Coração de estudante: educação musical na sala de aula - Paiva, Luís Alberto dos Santos (2023)
This study presents the strategies adopted in high school art classes at the Escola de Tempo Integral do Estado do Maranhão in 2022, to introduce music in an inclusive and comprehensive way, facing difficulties such as the lack of a specific curriculum for teaching music. music and the few hours dedicated to the discipline of Arts. Such actions provided opportunities for all students, and not only those who had musical skills, to develop musicality through collective singing, body percussion, introduction to music theory and analysis of lyrics. To that extent, itprovided the students with contact with the diversity of brazilian popular music, which they donot usually access because it is not present in the mainstream media, but which is rich in meaning and aesthetics capable of sensitizing them and draw them deeply, as we havewitnessed. Thus, the actions adopted dialogued with those used by music educators such as Villa-lobos, Koellreutter and Murray Schafer. In addition, we draw reflections, adopting the Habitus’s concept and cultural capital’s concept by Pierre Bourdieu, as well as the concept of Cultural Industry, by Adorno and Horkheimer, to present a proposal for musicalization in the art class of public schools.